Nodules biomass density in mixed and monospecific stands of Eucalyptus grandis x Eucalyptus urophylla and Acacia mearnsii - Viera, Márcio; Schumacher, Mauro Valdir; Liberalesso, Edenilson (Revista Ecologia e Nutrição Florestal - ENFLO, 2014)
We aimed to evaluate the distribution of the nodules biomass density in Acacia mearnsii at monospecific and mixed planting with Eucalyptus grandis x E. urophylla in southern region of Brazil. The nodules biomass quantification was performed at the stand 18th month of age. The collecting was made using a cylindrical steel extractor tube with 7.0 cm of inside diameter in four depths: 0 – 5; 5 – 10; 10 – 20 and 20 – 30 cm. Due to the great variability, the nodules biomass, although being much higher in the monospecific planting of Acacia mearnsii when comparing to mixed planting, did not show significant differences (p > 0.05). The greater nodules density was found in the layers 5 to 10 cm of depth, near to thetree trunk and at the planting line followed by the planting diagonal and row. The nodules biomass density found for the black-wattle (up to 2.4 g dm-3) demonstrates the importance of the use of this atmospheric nitrogen-fixing species in mixed plantings with eucalyptus. DOI: http://dx.doi.org/10.13086/2316-980x.v01n03a03